2014
DOI: 10.1128/aem.04105-13
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides and Proteins Added to Flowing Drinking Water at Microgram-per-Liter Levels Promote the Formation of Biofilms Predominated by Bacteroidetes and Proteobacteria

Abstract: Biopolymers are important substrates for heterotrophic bacteria in (ultra)oligotrophic freshwater environments, but information about their utilization at microgram-per-liter levels by attached freshwater bacteria is lacking. This study aimed at characterizing biopolymer utilization in drinking-water-related biofilms by exposing such biofilms to added carbohydrates or proteins at 10 g C liter ؊1 in flowing tap water for up to 3 months. Individually added amylopectin was not utilized by the biofilms, whereas la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…Cloning and sequencing of the 16S rRNA gene insert (ca. 650 bp) for identification of the predominating uncultured bacteria were performed as described previously (49). Counts of colonies with identical appearances on R 2 A agar were recorded as percentages of the total colony count.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cloning and sequencing of the 16S rRNA gene insert (ca. 650 bp) for identification of the predominating uncultured bacteria were performed as described previously (49). Counts of colonies with identical appearances on R 2 A agar were recorded as percentages of the total colony count.…”
Section: Methodsmentioning
confidence: 99%
“…Counts of colonies with identical appearances on R 2 A agar were recorded as percentages of the total colony count. Bacteria from predominating colonies were isolated, and the 16S rRNA genes of the isolates were amplified by PCR using primers 8f and 1392r (Biolegio, the Netherlands) (49). Fragments of approximately 1,030 bp were sequenced by using primer 8f.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been found in various marine habitats, including coastal sediments (3), coastal waters (4, 5), hydrothermal vents (6, 7), and open ocean waters (8-10). In previous studies, marine Bacteroidetes have been reported as important contributors to the utilization of biopolymers such as polysaccharides and proteins (2,(11)(12)(13)(14). As a result, marine Bacteroidetes are assumed to play an important role in the degradation of algae.…”
mentioning
confidence: 99%
“…Besides the complex competition for nitrogen and phosphorus between diatoms and bacteria, the amount of available organic carbon apparently strongly affects the entire biofilm food web. 81 Recent studies have given insights into highly specialized EPS utilization by bacteria 82 and discovered a strong regulatory role of these EPSs produced by diatoms upon bacterial development and activity. 83 In the context of nutrient limitation, the morphology of the microbes can be a decisive factor.…”
Section: Effects Of Light Intensitymentioning
confidence: 99%